Study on ground deformation in Kathmandu valley using C-band Sentinel-1a synthetic aperture radar (SAR) satellite images (Journal of Nepal Geological Society, 2025)
Interferometric synthetic aperture radar (InSAR) is a prominent and widely used remote sensing method used for accurate surface deformation across large areas. We applied this technique to study the subsidence and upliftment of the ground surface in Kathmandu Valley in the years between 2019 and 2023 AD. C-band Sentinel-1A images from 2019 to 2023 were employed in this study to investigate the status of ground deformation. This study highlights ground upliftment in major parts of the valley in the year 2022 and 2023 whereas the valley experienced major subsidence during the year 2020 to 2022. These results in agreement with prior studies of tectonic and anthropogenic influences suggest that ongoing tectonic compression combined with intensive groundwater withdrawal have driven the observed patterns. Because the valley lies deep, soft sedimentary fill even moderate ground motions pose hazards to infrastructure. We conclude that Kathmandu’s ground is actively deforming and recommend enhanced water resource management and land use planning to mitigate future subsidence risk. In this study we also found that the major subsidence was found in the central north region and southeastern part of the valley. But in the years between 2022 and 2023 major uplifting was found in the northern part of the valley. In general, the study shows major deformation over a four-year time interval which may have occurred due to the seismic movement or groundwater depletion.